Peran Gereja dalam Membina Moderasi Beragama Melalui Pelayanan Kesehatan Gratis di Cileungsi - Kurniawan, Martha Mulyani (Sekolah Tinggi Teologi Kadesi Bogor, 2024)
The government's efforts to implement public health programmes are very limited, given the country's limited financial conditions. The state budget is so much absorbed to win back public health. Not all public health costs are covered by BPJS/JKN and KIS, so not a few communities need help in this health.The Church has a role in the fulfilment of the great faith of Jesus Christ through the ministry that can be performed by the church as a manifestation of God's love that does not look at race, tribe, language and religion, but rather does as Jesus did for the glory of His name and the presence of the church can be a blessing to the priests around the church. The cooperation between the church and the shepherds and herdsmen under the patronage of the BKSG of Bogor district, which has a community care program in terms of health and has collaborated with the partners of the hospitals in Bogor District, is an attempt to preach the great faith of Jesus Christ in helping the people to carry out free health services so that the church can help the people and the government to create a healthy, tolerant society so that a congregation of religious people is created as proof that the Indonesian nation is a nation that has differences but remains united under the umbrella of Pancasila and UUD 1945.